On the analytical optical soliton solutions of perturbed Radhakrishnan-Kundu-Lakshmanan model with Kerr law nonlinearity - Ozisik, Muslum; Secer, Aydin; Bayram, Mustafa; Yusuf, Abdullahi; Sulaiman, Tukur Abdulkadir (SPRINGER, 2022)
This paper carries out the analytical optical soliton solutions of perturbed Radhakrishnan-Kundu-Lakshmanan (pRKL) equation with Kerr law nonlinearity using an efficient modified extended tanh expansion method, enhanced with the new Riccati solutions (eMETEM). In this study, we have established robust solutions for the pRKL by using the eMETEM method for the first time. We have focused to construct the effective scheme for the solution of governing model. Bright, dark, combined bright-dark, singular, multiple singular, flat kink-like, breather-like, periodic, different periodic optical solitons have been successfully obtained and confirmed with the help of Maple and Matlab symbolic computation packages. The physical properties of the data have been discussed and presented in 3D, 2D and contour graphics. The results have also been interpreted in the relevant sections.
Keywords: Perturbed Radhakrishnan-Kundu-Lakshmanan equation; Soliton solutions; Enhanced modified extended tanh method; SPATIOTEMPORAL DISPERSION; SCHRODINGER-EQUATIONS; TANH METHOD; POWER; FIBERS; Engineering; Physics; Optics